Therapeutic conduct in front of dental care of different age groups: literature review (Research, Society and Development, 2021)
The aim of this study is to carry out a bibliographical review addressing the main obstacles and challenges faced by the Dental Surgeon facing different age groups in dental care. The study is classified as a narrative literature review, with an exploratory character and a qualitative approach. Based on this permission, a search was carried out in the main world science and health databases, such as: Pubmed, Bireme, Scielo, Libary and Lilacs, applying as the main filter publications ranging from 2016 to 2021, written in Portuguese and English, thus enabling the realization of an updated approach on the proposed theme. The selection complied with the inclusion and exclusion criteria of the articles presented, so after reading the title, abstract, and full content of each of the studies, 27 articles were selected, used as a theoretical basis for this review. It is concluded that the general role of the Dentist-Surgeon (CD) is a challenge, considering that the multidisciplinary care requires a mastery of the professional CD about different specialties and also the age groups, considering that the chronological age of a patient can directly influence the method used to perform the dental care.